Comparison of four new commercial serologic assays for determination of SARS-CoV-2 IgG (2020)
Background Facing the ongoing pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), there is an urgent need for serological assays identifying individuals with past coronavirus disease 2019 (COVID-19). Study design Our study is the first to compare four new commercially available assays using 75 sera from patients tested positive or negative by SARS-CoV-2 PCR: the anti SARS-CoV-2 ELISA (IgG) (Euroimmun, Germany), the EDI New Coronavirus COVID-19 IgG ELISA, (Epitope diagnostics (EDI), USA), the recomWell SARS-CoV-2 IgG ELISA (Mikrogen, Germany), and the SARS-CoV-2 Virachip IgG (Viramed, Germany). Results We found a sensitivity of 86.4 %, 100 %, 86.4 %, and 77.3 % and a specificity of 96,2 %, 88,7 %, 100 %, and 100 % for the Euroimmun assay, the EDI assay, the Mikrogen assay, and the Viramed assay, respectively. Conclusions Commercially available SARS-CoV-2 IgG assays have a sufficient specificity and sensitivity for identifying individuals with past SARS-CoV-2 infection.